THE STUDY OF THE RELATIONSHIP BETWEEN MACROECONOMIC FACTORS AND THE COUNTRY'S ECONOMIC DEVELOPMENT IN THE CASE OF FRANCE (Web of Teachers: Inderscience Research, 2025)
This study examines the relationship between key macroeconomic factors and the economic development of France, with a focus on GDP per capita as the primary indicator of growth. Using Stata software, we analyzed the impact of several variables, including industry output, foreign direct investment (FDI), unemployment rate, exchange rate, and interest rate on GDP per capita. Two econometric models were employed: Ordinary Least Squares (OLS) to assess the direct linear relationships, and a Vector Autoregression (VAR) model to capture dynamic interactions between the variables.